Trigonometry kills! (4)

Calculus Level 4

π π 2 x ( 1 sin x ) 1 + cos 2 x d x \large \int_{-\pi}^\pi \dfrac{2x(1-\sin x)}{1+\cos^2 x} \, dx

Compute the integral above. Give your answer up to 3 decimal places.

For your final step, use the approximation, π = 22 7 \pi = \dfrac{22}7 .


The answer is -9.877551.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

π π 2 x 1 + cos 2 x . d x = 0 \large \displaystyle \int_{-\pi}^{\pi} \frac{2x}{1 + \cos ^2x} .dx = 0 , Since it is odd function.

Hence, Required integral

= π π 2 x sin x 1 + cos 2 x . d x = 4 0 π x sin x 1 + cos 2 x . d x = 4 I = \large \displaystyle \int_{-\pi}^{\pi} \frac{-2x \sin x}{1 + \cos ^2x} .dx = - 4 \large \displaystyle \int_{0}^{\pi} \frac{x \sin x}{1 + \cos ^2x} .dx = -4I

Now, I = 0 π x sin x 1 + cos 2 x . d x = 0 π ( π x ) sin ( π x ) 1 + cos 2 ( π x ) . d x \large \displaystyle I = \int_{0}^{\pi} \frac{x \sin x}{1+ \cos ^2x} .dx = \int_{0}^{\pi} \frac{(\pi - x) \sin (\pi -x)}{1+ \cos ^2(\pi -x)} .dx

2 I = π 0 π sin x 1 + cos 2 x . d x = π [ tan 1 ( 1 ) tan 1 ( 1 ) ] = π 2 2 \large \displaystyle \implies 2I = \pi \int_{0}^{\pi} \frac{\sin x}{1+ \cos ^2x} .dx = - \pi \left[\tan ^{-1} (-1) - \tan^{-1} (1) \right]\\ \large \displaystyle = \frac{\pi ^2}{2}

I = π 2 4 \large \displaystyle \implies I = \frac{\pi ^2}{4}

Given Integral = π 2 = 22 × 22 7 × 7 = 9.877551 \large \displaystyle \therefore \text{Given Integral} = - \pi ^2 = - \frac{22 \times 22}{7 \times 7} = -\boxed{9.877551}

Kindly check your third step. Answer for I comes out -pi * pi/4 and not pi * pi/4

vinayak nayak - 5 years, 2 months ago

Log in to reply

Boss its correct.

Samara Simha Reddy - 5 years, 2 months ago
Aareyan Manzoor
Apr 21, 2016

I = π π 2 x ( 1 sin x ) 1 + cos 2 x d x = 0 π 2 x ( 1 sin x ) 1 + cos 2 x d x + π 0 2 x ( 1 sin x ) 1 + cos 2 x d x I=\int_{-\pi}^\pi \dfrac{2x(1-\sin x)}{1+\cos^2 x} dx=\int_0^\pi \dfrac{2x(1-\sin x)}{1+\cos^2 x} dx+\int_{-\pi}^0\dfrac{2x(1-\sin x)}{1+\cos^2 x} dx changing x with -x in the latter integral we have I = 0 π 2 x ( 1 sin x ) + 2 ( x ) ( 1 sin ( x ) 1 + cos 2 x d x = 0 π 4 x s i n ( x ) 1 + cos 2 x d x I=\int_0^\pi \dfrac{2x(1-\sin x)+2(-x) (1-\sin(-x)}{1+\cos^2 x} dx= \int_0^\pi \dfrac{-4xsin(x)}{1+\cos^2 x} dx using integration by parts (use d d x arctan ( cos ( x ) ) = sin x 1 + cos 2 x \frac{d}{dx} \arctan(\cos(x))= \dfrac{-\sin x}{1+\cos^2 x} ) to get I = 4 x a r c t a n ( cos ( x ) ) 0 π 4 0 π arctan ( cos ( x ) ) d x = π 2 4 0 π arctan ( cos ( x ) ) d x I=4x arctan(\cos(x)) |_0^\pi- 4 \int_0^\pi \arctan(\cos(x)) dx=-\pi^2-4\int_0^\pi \arctan(\cos(x)) dx let k = 0 π arctan ( cos ( x ) ) d x = 0 π arctan ( cos ( π x ) ) d x = 0 π arctan ( cos ( x ) ) d x = k k = 0 k=\int_0^\pi \arctan(\cos(x)) dx = \int_0^\pi \arctan(\cos(\pi-x)) dx = \int_0^\pi \arctan(-\cos(x)) dx=-k\to k=0 so, I = π 2 I=-\pi^2

Moderator note:

Good approaches used here to simplify the expression.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...